2018
DOI: 10.1021/acs.jpcb.7b11094
|View full text |Cite
|
Sign up to set email alerts
|

DNA–Polyelectrolyte Complexation Study: The Effect of Polyion Charge Density and Chemical Nature of the Counterions

Abstract: Complexes of polycations and DNA, also known as polyplexes, have been extensively studied in the past decade, as potential gene delivery systems. Their stability depends strongly on the characteristics of the polycations, as well as the nature of the added salt. We present here a study of the DNA ionene complexation in which we used fluorescence, UV, and CD spectroscopy, combined with molecular dynamics computer simuations, to systematically examine the influence of the polycation charge density, as well as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 47 publications
(105 reference statements)
0
15
0
Order By: Relevance
“…The MD simulation of the DNA-CAAIL ligand system in aqueous medium was performed to investigate the structural dynamics of the DNA−ligand interaction, as well as the relative population of various modes of binding of the ligand. Mojca et al 63 in their recent article showed the influence of charge density of ionene in the stability of DNA and found negligible effect of ionene anion on DNA binding by combined study of experimental and theoretical calculation. Chandran et al 9 through spectroscopic and MD simulation results suggest that electrostatic, hydrophobic, and polar interactions of IL cations play significant role in DNA stability.…”
Section: B) All Three Caails [Ch][gly] [Ch][ala] [Ch]mentioning
confidence: 99%
“…The MD simulation of the DNA-CAAIL ligand system in aqueous medium was performed to investigate the structural dynamics of the DNA−ligand interaction, as well as the relative population of various modes of binding of the ligand. Mojca et al 63 in their recent article showed the influence of charge density of ionene in the stability of DNA and found negligible effect of ionene anion on DNA binding by combined study of experimental and theoretical calculation. Chandran et al 9 through spectroscopic and MD simulation results suggest that electrostatic, hydrophobic, and polar interactions of IL cations play significant role in DNA stability.…”
Section: B) All Three Caails [Ch][gly] [Ch][ala] [Ch]mentioning
confidence: 99%
“…Important insight on the interactions of nucleic acids with polycationic polymers can already be obtained by using simple model systems of rather limited sizes compared to corresponding experimental systems (27,28,53,54). However, considering that the focus on this study is on the effect of the relative amount of the "stealth" agent vs the polycation on the binding to DNA, and that charge polymers "end effects" are known to affect the electrostatic interactions, we did limit the gap between the computational and experimental systems, by using vector and DNA molecule of the same size in the "in vitro" and "in silico" experiments.…”
Section: Discussionmentioning
confidence: 99%
“…The stability of polyplex films based on DNA depends strongly on the characteristics of the polycations, as well as the nature of the added salt [149,150]. Binding interactions between DNA and cationic nanocarriers must be sufficiently strong to prevent nuclease-mediated degradation, yet weak enough to permit transcription [42].…”
Section: Pe-nucleic Acid Hybrid Layersmentioning
confidence: 99%